Wet chemical preparation of CdS nanoparticles for the photodetection application. (2023) - Kumar, Abhishek; Verma, Arpit; Singh, Ajeet; Yadav, B.C.
Highlights: CdS nanostructures synthesised by simple wet chemical approach. The crystallite size is observed to 11.5 nm and Tauc plot gives the optical band gap energy of 3.13 eV. This MSM device exhibited the high performance photodetection parameters. Photoresponsivity is observed to 35.78 mA/W. Detectivity is observed to 2.23 × 10 10 Jones. Abstract: In this investigation, CdS nanoparticles were prepared for utilisation in the CdS-based photodetector device. X-ray diffraction (XRD), Scanning electron microscopy (SEM), Ultraviolet–visible (UV–vis) absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy, and Dynamic light scattering (DLS) were used to analyse the properties of CdS nanoparticles. By using the standard Scherrer formula, the crystallite size was found to be 11.5 nm and Tauc plot gave the optical band gap energy of 3.13 eV. The dynamic light scattering experiment suggests that most of the particles are distributed in the range of 1–150 nm. Excellent photodetection parameters were observed during the photodetection experiments. The observed photoresponsivity was found to 35.78 mA/W with the detectivity of 2.23 × 10 10 Jones. This photodetector device also shows the external quantum efficiency of 12.13 % with a noise equivalent power of 8.97 × 10 -6 W.